Characterization of peanuts after dry roasting, oil roasting, and blister frying. (January 2017) - Shi, Xiaolei; Davis, Jack P.; Xia, Zhoutong; Sandeep, K.P.; Sanders, Timothy H.; Dean, Lisa O.
Abstract: Peanuts were systematically deep fried, blister fried, or dry roasted at 177 °C to Hunter L-values of 53.0 ± 1.0, 48.5 ± 1.0, and 43.0 ± 1.0, corresponding to light, medium, and dark roasting, respectively. Thermal modifications of the epidermal and parenchyma cells were observed in the scanning electron microscopic images for processed peanuts, compared to raw peanuts. Peanut microstructure was most extensively damaged by blister frying, followed by deep frying, and then dry roasting. The moisture content decreased with increased surface color, due to more moisture loss with longer heat processing time. For light roasting, blister fried peanuts had significantly higher moisture contents than the deep fried and dry roasted peanuts, while for medium and dark roasting, blister fried had lower moistures than the other two. Descriptive sensory analysis was able to distinguish the flavor and texture profiles of peanuts prepared by different roasting methods. In storage testing throughout 16 weeks, peroxide value measurements indicated the blister fried peanuts had the longest shelf life, followed by the dry roasted, and then the deep fried. Descriptive sensory analysis proved that the rate of the loss of roast peanut flavor during storage was faster in dry roasted peanuts followed by blister fried and deep fried. Highlights: Peanut processing methods gave equivalent colors by varying the time at the same temperature. Quality-related peanut properties were affected by different thermal processing methods. This pilot plant design has industrial application for production of high quality roasted peanuts.